Effect of Ambient Sunlight Intensity on the Temporal Phenolic Profiles of Vitis Vinifera L. Cv. Chardonnay During the Ripening Season – A Field Study - Å ebela, D.; Turóczy, Z.; Olejníčková, J.; KumÅ¡ta, M.; Sotolář, R. (South African Journal of Enology and Viticulture, 2017)
Grape phenolics are considered to have a significant impact on wine quality, with their quantity and dynamics being strongly influenced by environmental conditions. We investigated the effect of ambient sunlight on the temporal dynamics of phenolics in cv. Chardonnay under field conditions during the 2012 ripening season, from véraison until harvest. The phenolic profiles of the grapes were monitored at predefined time intervals by using high-pressure liquid chromatography (HPLC) and spectrophotometric (OD) analysis. The obtained concentrations were correlated with the average sunlight intensities preceding the sampling. No significant correlations were found between the hydroxycinnamic acid, hydroxybenzoic acid and stilbene content, in contrast with the strong relationships found between: (i) OD280 nm, (ii) catechin, (iii) flavanols and (iv) total polyphenols and the fluctuating dose of ambient sunlight reaching the grapes throughout the ripening season. The light-dependent dynamics of several main phenolic compounds in cv. Chardonnay during the ripening period could help to establish correlation models that increase the applicability of meteorological data in the assessment of optimal phenolic ripeness in modern viticulture.